2021
DOI: 10.3390/jcm10245766
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Bedside Placement of Tunneled Hemodialysis Catheters in the Intensive Care Unit: Translating from the COVID-19 Experience

Abstract: Background: Critically ill patients with coronavirus disease 2019 (COVID-19) and kidney dysfunction often require tunneled hemodialysis catheter (TDC) placement for kidney replacement therapy, typically under fluoroscopic guidance to minimize catheter-related complications. This entails transportation of patients outside the intensive care unit to a fluoroscopy suite, which may potentially expose many healthcare providers to COVID-19. One potential strategy to mitigate the risk of viral transmission is to inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Aurshina et al [13] reported on 1065 patients who underwent surgery under ultrasound guidance, among whom there were no cases of severe complications such as hemothorax or pneumothorax, with only 2 cases of arterial injury and 3 cases requiring post-operative revision due to incorrect catheter placement. Sohail et al [14] reported on 25 cases during the COVID-19 pandemic where institutions that routinely used DSA for placement changed their approach to ultrasound guidance, achieving a 100% success rate with post-operative blood ow and ultra ltration meeting the requirements of dialysis prescriptions.However, there is currently a lack of studies comparing the placement of hemodialysis catheters under DSA and ultrasound guidance. The references for DSA and ultrasound guidance for TDC placement surgery in KDIGO 2019 are sourced from an article published by Yevzlin et al [15] in 2007, which only reported higher surgical success rates and lower costs under DSA guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Aurshina et al [13] reported on 1065 patients who underwent surgery under ultrasound guidance, among whom there were no cases of severe complications such as hemothorax or pneumothorax, with only 2 cases of arterial injury and 3 cases requiring post-operative revision due to incorrect catheter placement. Sohail et al [14] reported on 25 cases during the COVID-19 pandemic where institutions that routinely used DSA for placement changed their approach to ultrasound guidance, achieving a 100% success rate with post-operative blood ow and ultra ltration meeting the requirements of dialysis prescriptions.However, there is currently a lack of studies comparing the placement of hemodialysis catheters under DSA and ultrasound guidance. The references for DSA and ultrasound guidance for TDC placement surgery in KDIGO 2019 are sourced from an article published by Yevzlin et al [15] in 2007, which only reported higher surgical success rates and lower costs under DSA guidance.…”
Section: Discussionmentioning
confidence: 99%
“…In such a scenario, initially in the former cases (about 30 to 40 cases), the appropriate catheter length site was estimated based on the patient's height, as well as measurements on the patient's recent chest X-ray. In the later 50 to 60 cases, we used the manubrial-sternal angle (angle of Louis) as a topographical landmark for the carina [1,5]. The estimated insertion depth was selected by adding the distance between the puncture site and a point 5 cm below the manubrial-sternal angle.…”
Section: Catheter Insertion Techniquesmentioning
confidence: 99%
“…Ultrasound and fluoroscopy-guided punctures are recommended for safe procedures when performing catheter insertion including hemodialysis (HD) catheters. However, for unstable patients, such as those on a ventilator in an intensive care unit (ICU), transferring the patient to the fluoroscopy is subject to constraints, sometimes worsening the patient's condition in the process [1]. ICU patients Safety and durable patency of tunneled hemodialysis catheter inserted without fluoroscopy receiving critical care often require renal replacement therapy (RRT).…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 During COVID era, successful and safe bedside placement of tunneled CVC using anatomic landmarks has been reported. 9 Recently, for tunneled dialysis CVC, a technique using agitated saline for localization of the catheter tip near the atrium has been described. 10 , 11 …”
mentioning
confidence: 99%